Pre-British Indian Economy and Self-Sufficient Village Community (It’s Impact on Indian National Movement) - Tyagi, Bhuwneshwer Kumar (Journal of Commerce and Trade, 2010)
Through this study we can go back to the pre-British times of Indian life and study how the self-sufficient village community has been transformed drastically, and evolved as that of today in about 200 years. Enthusiastically one can consider the deeper aspects of British rule over India than mere political domination, and search into the socio-cultural change that has taken place in the overall life of a people, the people of India, a country that was once called ‘the golden bird.’ It takes up four important sectors of socio-cultural and economic life of the Indians viz., agriculture, small-scale industry, education, and politics and administration, and tries to establish how the British conquest affected these areas as far as Indian life is concerned.